1851 Terr. of N.M. Laws 10 - (:unkn) unknown (My University, 1851)
An Act Incorporating the City of Santa Fe, § 7: The board of common councilors shall have power to pass By-Laws and Ordinances . . . to prohibit the firing of fire-arms . . . to regulate and prescribe the quantities and places in which gun-powder or other dangerous combustible[s] may be kept[.]
Keywords: DISCHARGE; GUNPOWDER - STORAGE